Preparation of polymer films containing multi-branched chromophores for enhanced nonlinear optical activity. (January 2017) - Lin, Wenxin; Cui, Yuanjing; Yu, Jiancan; Yang, Yu; Qian, Guodong
Abstract: Two new multi-branched chromophores were synthesized via esterification from monochromophores to achieve ideal macroscopic nonlinear optical activities. Molecular chemical structures of chromophores were confirmed by 1 H NMR, FT-IR spectroscopy, elemental analysis, mass spectrometry and UV–visible absorption spectra. MonochromophoreN1 and bichromophoreDN were doped into poly (4-vinylphenol) to fabricate guest-host polymer filmsFilm-N1 andFilm-DN with high molecular loading density (up to 30 wt%). And the maximum second harmonic generation coefficients ( d 33 ) of polymer filmsFilm-N1 andFilm-DN reached to 25 pm V −1 and 39 pm V −1, respectively. In contrast, six-branched dendritic chromophoreSN was utilized directly to prepare thin filmFilm-SN without any polymer matrix due to its large molecular weight (about 3183 Da) and the d 33 value ofFilm-SN was up to 208 pm V −1 . Compared withFilm-N1, films containing multi-branched chromophoresFilm-DN andFilm-SN exhibited about 1.6-fold and 8.3-fold enhancement in the d 33 value indicating the multi-branched chromophore could significantly promote the macroscopic optical nonlinearity through the site-isolation effect. Highlights: Two new multi-branched chromophoresDN andSN were synthesized. Polymer filmsFilm-N1, Film-DN andFilm-SN were prepared with high active chromophore density. Thin filmsFilm-DN andFilm-SN exhibited enhanced d 33 value.